Body Mass Index and Long-Term Outcomes in Patients With Colorectal Cancer - Shahjehan, Faisal; Merchea, Amit; Cochuyt, Jordan J.; Li, Zhuo; Colibaseanu, Dorin T.; Kasi, Pashtoon Murtaza (Frontiers in Oncology, 2018)
Background: The association between body mass index (BMI) and colorectal cancer is unique. There are several patient- and tumor-related factors that affect this and associations are not entirely clear. The primary aim of this study is to examine the association between BMI and survival after colorectal cancer diagnosis. Methods: Among 26,908 Mayo Clinic patients diagnosed with colorectal cancer between 1972 and 2017, 3,799patients had information on BMI within 6 months prior to cancer diagnosis. Multivariable Cox regression models were used to assess the differences in overall survival between BMI groups in each cancer stage, controlling for age, gender, year of diagnosis and cancer location. The impact of change of BMI at 30, 60 and 90 day on survival afterwards were also analyzed. Results: Among 3,799 patients included in the study, there were 29% normal weight, 2% underweight, 36% overweight and 33% obese patients. With all stages combined together, the overall 5-year survival rates for underweight, normal weight, overweight and obese patients were 33%, 56%, 60% and 65% respectively (p<0.001). The results show that, the difference in overall survival was not statistically significant when underweight, overweight and obese patients were compared to normal weight patients in stage 1 and stage 2, although there was a trend that overweight patients had better survival than normal weight group in stage 2 cancer patients (HR = 0.8, p=0.086). In stage 3 and 4 patients combined, underweight group demonstrated a significant disadvantage (HR=1.96, p=0.007) for overall survival compared to the normal weight group. Additionally, post-diagnosis BMI drop more than 10% from either a previous time (HR=1.88, p=0.002) or pre-diagnosis time (HR=1.61, p<0.001) was associated with worse overall survival after adjusting for baseline variables. Conclusions: BMI is an important consideration in patients with colorectal cancer. Outcomes are stage-dependent where in some situations obesity maybe an advantage. More importantly, being underweight is a significant negative predictor of outcome. The impact of drop in BMI or weight, on survival of CRC patients, needs to be studied further since this is potentially an actionable variable and a dynamic biomarker that may help improve outcome in these patients.